Pengaruh Model Pembelajaran Kooperatif dengan Pendekatan Problem Posing Ditinjau dari Pengetahuan Awal Terhadap Kemampuan Pemecahan Masalah Fisika Siswa SMK - Jannah, Siti Nurdatul; Doyan, Aris; Harjono, Ahmad (Jurnal Pendidikan Fisika dan Teknologi, 2017)
This study aims to determine the effect of cooperative learning through problem posing approach to the studentsÃ¢â¬â¢ problem solving skills in terms of prior knowledge. The method used is a quasi-experimental method with 2x2 factorial study design. The study population was 163 students of class XI SMKN 9 Mataram scattered in 5 classes. These samples included 55 students, divided into two classes by cluster of random sampling technique. The research instrument is a test mastery of concepts and problem solving skills test given at the beginning and end of the study. The data was analyzed by Manova two ways. (1) students learn to use cooperative learning model with problem posing approach was significantly different in the aspect of problem solving ability than students who study with learning cooperative model only, (2) students who have high prior knowledge different significantly in aspects of problem solving ability compared students who have low prior knowledge, (3) there was not an interaction effect between learning model with prior knowledge of the problem solving ability students